Stereoselective synthesis of the polyketide chain of nagahamide A - Mohapatra, Debendra K.; Chaudhuri, Siddhartha Ray; Sahoo, Gokarneswar; Gurjar, Mukund K. (Tetrahedron-Asymmetry, 2006)
A carbohydrate based approach for the enantioselective synthesis of the polyketide acid unit present in nagahamide A has been reported. Reductive ring opening of a chiral cyclopropane ketone group to enantioselectively install the methyl and propyl groups, is a salient feature of this synthesis. (c) 2006 Elsevier Ltd. All rights reserved.

Synthesis of L-ido-configured six- and seven-membered carba-sugars - Ramana, C. V.; Chaudhuri, Siddhartha Ray; Gurjar, Mukund K. (Synthesis-Stuttgart, 2007)
Ring-closing olefin metathesis has been successfully applied to the modular construction of L-ido-configured six- and seven-membered carba-sugars.
Keywords: allylations; carbocycles; carbohydrates; Metathesis; Radical reactions